The Testing Model of Financial Management Ability of Small and Medium Enterprises (SMEs) - Maya Sari; Irfan Irfan; Jufrizen Jufrizen; Leni Deli (Universitas Muhammadiyah Malang, 2020)
This research aims to know the effect of financial literacy directly or indirectly through financial management of SMEs in Medan city by financial inclusion. The research uses quantitative method to associative approach with the data technic analysis using path analysis. Data were complied through questionnaries, interviews and documentation from a sample of 205 SMEs. The result of the research concludes that financial literacy affects to financial inclusion, the financial inclusion affects to the financial management ability, financial literacy affects to the financial management ability positively and significantly. Financial literacy also affects to financial management on SMEs in Medan city directly or indirectly. The limitation of this study is the lack of empirical research of SMEs in Medan city. The Implications of this research is that SMEs in maintaining and developing business competition in the future.